Fragmentasi Otoritas Dalam Proses Sertifikasi Halal dan Implikasinya Terhadap Perlindungan Konsumen di Indonesia - Christine, Gabriela (Riviera Publishing, 2025)
This research examines the fragmentation of authority in the halal certification process in Indonesia and its implications for consumer protection. With the enactment of Law No. 33 of 2014 on Halal Product Assurance (UU JPH), the authority to issue halal certification has shifted from a centralized system under the Indonesian Ulema Council (MUI) to a more decentralized model involving the Halal Product Assurance Agency (BPJPH) and other actors like the Halal Inspection Agency (LPH) and Halal Assistance Officers (Pendamping PPH). This study aims to analyze the legal framework surrounding this fragmentation and its impact on ensuring consumer rights and product integrity. By exploring the legal structure and implications of these changes, the research highlights the challenges in maintaining consistent standards and safeguarding public trust. The study suggests that the fragmentation of authority may lead to potential issues in the certification process, including overlapping responsibilities and concerns about the quality control of halal products, which can negatively affect consumer protection.